2021
DOI: 10.1007/s00220-021-04055-5
|View full text |Cite
|
Sign up to set email alerts
|

Spin(7) Instantons and Hermitian Yang–Mills Connections for the Stenzel Metric

Abstract: We use the highly symmetric Stenzel Calabi–Yau structure on $$T^{\star }S^{4}$$ T ⋆ S 4 as a testing ground for the relationship between the Spin(7) instanton and Hermitian–Yang–Mills (HYM) equations. We reduce both problems to tractable ODEs and look for invariant solutions. In the abelian case, we establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…In particular, this shows that deformed Spin(7)-instantons are not equivalent to dHYM connections with phase 1 when M has holonomy contained in SU(4) but is non-compact; this is rather different from the compact situation as shown by Kawai-Yamamoto in [23,Theorem 7.5], see also Theorem 2.4 (2) below. An analogous result was shown by Papoulias in [31] where the author showed that Spin(7)-instantons and traceless HYM connections do not coincide on the Calabi-Yau manifold T * S 4 ; this is again in contrast with the compact case as demonstrated by Lewis in [28,Theorem 3.1], see also [23,Remark 7.6]. This discrepancy is essentially due to the fact that the arguments in the compact cases in [23] and [28] both rely on certain energy estimates and these do not hold in the non-compact setting.…”
Section: Introductionsupporting
confidence: 87%
“…In particular, this shows that deformed Spin(7)-instantons are not equivalent to dHYM connections with phase 1 when M has holonomy contained in SU(4) but is non-compact; this is rather different from the compact situation as shown by Kawai-Yamamoto in [23,Theorem 7.5], see also Theorem 2.4 (2) below. An analogous result was shown by Papoulias in [31] where the author showed that Spin(7)-instantons and traceless HYM connections do not coincide on the Calabi-Yau manifold T * S 4 ; this is again in contrast with the compact case as demonstrated by Lewis in [28,Theorem 3.1], see also [23,Remark 7.6]. This discrepancy is essentially due to the fact that the arguments in the compact cases in [23] and [28] both rely on certain energy estimates and these do not hold in the non-compact setting.…”
Section: Introductionsupporting
confidence: 87%